Avaliação do equilíbrio de atletas de MMA antes e após combate: estudo descritivo transversal observacional - Gomes, Jaqueline da Silva (Brasil, 2024)
The aim of this study was to evaluate balance variations in MMA athletes before and after a fight in the municipality of Coari-AM. This was a descriptive cross-sectional observational study. The study consisted of 17 MMA athletes aged between 18 and 35 years old, who took part in a fighting event covering different categories. All the participants were assessed using the Wii Balance Board (WBB) before and after the fight. The balance of the athletes was analyzed by comparing the differences between athletes in relation to the outcome of the fights, as well as in relation to the difference in category related to weight. Data analysis was carried out using the Shapiro-Wilk test, as well as homogeneity using the Levene test. Differences were verified using the ANOVA test and Tukey's test, with a significance level of p < 0.05. The data was analyzed using Jamovi Training (version 2.2.5 for Windows). It was found that the winners, drawers and losers of the fights and from different categories showed greater imbalance after the fights, with a significant intra-group difference, but there was no significant inter-group difference. It can be concluded that MMA fights can change athletes balance, regardless of the result and category.